2016
DOI: 10.1037/bar0000046
|View full text |Cite
|
Sign up to set email alerts
|

Can humanoid robots serve as patient simulators in behavior analytic research and practice?

Abstract: Using a humanoid robot to simulate patient behaviors in research that involves staff– or caregiver–patient interactions can be highly valuable to behavior analysts. As a first step in using a robotic patient simulator in behavior analytic research, we examined whether trainees (college-aged adults) taught to conduct a common behavioral procedure responded similarly to a humanoid robot as to a research assistant acting as a patient. In both Studies 1 and 2, we found that participants (total of 9 undergraduate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Humanoid robots have served as an operandum for college students to rehearse newly learned preference assessment procedures (Kazemi & Stedman-Falls, 2016). However, robots have not been used to mediate behavior change procedures that a trainer implements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanoid robots have served as an operandum for college students to rehearse newly learned preference assessment procedures (Kazemi & Stedman-Falls, 2016). However, robots have not been used to mediate behavior change procedures that a trainer implements.…”
Section: Discussionmentioning
confidence: 99%
“…The Kazemi and Stedman-Falls (2016) study showcased one of the only demonstrations of using humanoid robots to train ABA practitioners. A noteworthy aspect of the Kazemi and Stedman-Falls study was that the experimenters, not the robots, provided feedback.…”
mentioning
confidence: 99%
“…It is possible that the fourth iteration of computing, including virtual reality, robotics, and others (e.g., self-driving cars), marks the next frontier of EAHB research. Some researchers have already begun demonstrating the unique application and advantages of such technological advancements (e.g., Kazemi & Stedman-Falls, 2016; North & North, 2016; Pritchard, 2010). To date, EAHB and technological advancements have sustained a steady relationship, and we believe that further advances will continue to be leveraged to improve EAHB research.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging fields of artificial intelligence and robotics could have implications for how future EAHB studies are conducted. For example, Kazemi and Stedman-Falls (2016) suggested that robots could serve as effective patient simulators during behavioral assessments and that the use of robots during assessment was rated favorably by participants. Indeed, if robots could serve as patient simulators, this could have long-lasting implications for EAHB (e.g., studying side effects of extinction of a robot programmed to engage in analogue problem behavior instead of using actual patients who engage in problem behavior could minimize risk of harm during the course of the experiment).…”
Section: Artificial Intelligence and Roboticsmentioning
confidence: 99%
“…(2010. Kazemi & Stedman-Falls (2016) demonstrated that the use of a humanoid robot was effective at teaching students how to implement preference assessments correctly.…”
Section: Of 13mentioning
confidence: 99%